2017
DOI: 10.1007/s00586-017-5362-6
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous posterolateral approach for the simulation of a far-lateral disc herniation in an ovine model

Abstract: Inducing a reproducible injury pattern of disc degeneration required minimal time, effort, and equipment. The posterolateral approach allows operation on several discs within a single surgery and multiple animal surgeries within a single day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 32 publications
(49 reference statements)
0
17
1
Order By: Relevance
“…Oehme et al 15 reported operation times of 60 min per animal, four times longer than our proposed method. In contrast to a previous study using this same methodology, 16 no animals showed any neurological deficits following surgery. However, this may be partially attributable to the JOURNAL OF ORTHOPAEDIC RESEARCH ® NOVEMBER 2019 cumulative experience of the operating surgeon, who also conducted the surgeries in the previous study.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Oehme et al 15 reported operation times of 60 min per animal, four times longer than our proposed method. In contrast to a previous study using this same methodology, 16 no animals showed any neurological deficits following surgery. However, this may be partially attributable to the JOURNAL OF ORTHOPAEDIC RESEARCH ® NOVEMBER 2019 cumulative experience of the operating surgeon, who also conducted the surgeries in the previous study.…”
Section: Discussioncontrasting
confidence: 99%
“…Prior to the first operation, each animal's overall and spine health was assessed in a general physical examination. During the first surgery, one lumbar IVD per animal was damaged via partial nucleotomy according to the previously described method . Figure A shows the surgical tools used for the operation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations